Frege on the Ontological Presuppositions of Scientific Discourse - Greimann, Dirk (Princípios: Revista de Filosofia (UFRN), 2022)
According to the standard conception of ontological commitment, which goes back to Quine, we are ontologically committed to acknowledge those and only those entities whose existence is a condition for the truth of our theories. Frege has sketched, in the context of his critique of the idealist interpretation of scientific language, a more complete approach according to which we are committed to accept also those entities whose existence is a condition for successful communication in science. He argued that we must acknowledge a Platonic realm of objective senses because the existence of such entities is a condition for communicating non-trivial scientific discoveries. The aim of this paper is to reconstruct and defend Frege’s approach. The main thesis defended is that, although Frege’s analysis of ontological commitment is largely obsolete, his general approach to derive our ontological commitments from both the truth and the success conditions of scientific discourse is correct.